The effect of screen time on auditory processing and working memory skills in tweens (pre-adolescents) - Saransh Jain; Rakesh Trinesh; Srikar Vijayasarthy; Sanjana S. Singh; Amuna Dangi; Chandni Jain (The Egyptian Journal of Otolaryngology)
Abstract Background This study investigates the impact of screen time on auditory processing and working memory in tweens, considering the subtle relationship proposed by the Goldilocks Hypothesis. The research aims to contribute insights into the potential effects of different screen exposure levels on auditory processing and working memory skills, recognizing the prevalence of screen use among tweens. Method Fifty-seven tweens were randomly selected and categorized into three groups based on their daily screen exposure. Auditory processing and working memory were assessed by measuring temporal resolution, auditory closure, binaural integration, and digit span tasks. Comprehensive screenings for hearing, speech, language, and IQ skills were conducted, ensuring the inclusion of tweens with normal hearing and cognitive functions. Results The study results revealed a non-linear relationship between screen time and auditory processing. Tweens with moderate screen exposure exhibited superior auditory processing skills, while high screen time was associated with deficits in temporal resolution, speech perception, binaural integration, and working memory. The Goldilocks Hypothesis was supported, indicating that too much screen time may have negative consequences, while too little exposure may not exploit the potential benefits of digital media usage. The findings emphasize the importance of moderation in screen time for optimal auditory processing and working memory in tweens. Prolonged screen exposure, especially beyond three hours daily, negatively affected auditory processing and working memory abilities. Conclusion The study highlights the need for a balanced approach to screen time, aligning with the broader literature on child development.